The Roles of Chinese CEOs in Managing Individualistic Cultures in Cross‐border Mergers and Acquisitions - Zhu, Hong; Zhu, Qi; Ding, Zhiwen (Journal of Management Studies, 2020)
AbstractThe individualism‐collectivism culture represents an important and well‐researched distinction across cultures. Yet research is less clear about how the different levels of individualistic cultures in host countries affect the success of an increasingly important firm strategy – cross‐border mergers and acquisitions (CBMAs). This study addresses this key research question in the context of Chinese firms’ CBMAs, as Chinese firms are increasingly acquiring targets outside of China in the New Normal global business landscape. This study further theorizes and tests how the Chinese acquirer CEOs’ characteristics moderate the wealth creation relationship. In an analysis of 404 Chinese firms’ CBMAs, we found that an individualistic culture in the host country is negatively associated with Chinese acquirers’ CBMA wealth creation. We also demonstrate that Chinese CEOs’ exposure to foreign culture and female gender weaken that negative relationship, while CEO duality strengthens this negative relationship. Our research thus suggests that culture in host countries can negatively affect acquirers’ CBMA performance, but CEOs may be able to manage the effects of the culture to increase their CBMA performance.